Pengaruh Promosi dan Sistem Pembayaran Cash On Delivery (COD) pada Aplikasi Tiktok Terhadap Tingkat Penjualan PT. Yishan Teknologi Indonesia - Arsila, Cahya Meta; Mardila, Mina; Rohmah, Yunita Nur; Prianto, Sukma Hadi; Yulianto (Maksimal Jurnal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
This research aims to determine the impact of the promotion and cash on delivery (COD) system in the TikTok application on the marketing level of PT. Yishan Technology Indonesia. The method used in this research is a quantitative survey with a random sampling method among consumers who use the TikTok application for shopping. Data were analyzed using multiple linear regression to determine the relationship between support variables, COD payment methods and sales levels. The research results show that these two changes have a positive and significant impact on increasing sales levels. Attractive promotions and ease of payment via COD have been proven to increase customer buying interest. These results provide important information for PT. Yishan Teknologi Indonesia which has made a good business plan on the TikTok platform.